Penurunan Nilai Kemanusiaan dengan Ancaman Simbolik: Studi Kasus Pengiriman Bangkai Tikus ke Redaksi Tempo - Shafina Aqila; Shavira Ayunaida; Kanaya Angelina (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study analyzes the symbolic threat against Tempo’s editorial team through the delivery of decapitated rat carcasses and a pig’s head in March 2025. The incident is interpreted as a symbolic act of intimidation that reflects a significant decline in human values, violating the principles of the second precept of Pancasila: “Just and Civilized Humanity.” Using a normative qualitative method, this research examines the symbolic meanings embedded in the threats and their impact on press freedom and social ethics in Indonesia. Employing the theory of symbolic interactionism, the study explains how the perpetrators used symbols not only to express hatred but also to dehumanize journalists and delegitimize critical media discourse. Findings indicate that such symbolic violence contributes to a broader culture of fear and normalization of repression, especially when the state fails to provide adequate protection for journalists. The case also illustrates the erosion of collective human values and the increasing public indifference a “bystander effect toward violations against freedom of expression. It is concluded that symbolic threats in the form of animal carcasses are not merely individual acts but reflect systemic attacks on press freedom and democratic ethics.